IMPLIKASI EKSEKUSI JAMINAN DOKUMEN RESI GUDANG KETIKA STOK DI GUDANG MENGHABIS - Tubalawony, Ansilla (JURNAL MEDIA HUKUM DAN PERADILAN, 2019)
This research aims to address the issue of legal protection of the recipient of Warehouse receipt assurance when the debtor is tort. Research using the approach of legislation and concept approaches, obtained the following conclusions: The document of the stock of goods in the warehouse is a valuable letter, because it has an economical value, because it can Used as a debt guarantee for banks. The stock in the warehouse often varies according to the stock supply, although in the form of moving goods, cannot be burdened with a pawn, requiring the delivery of goods that used as mortgage object, fiduciary guarantee, because it requires The submission of ownership rights, thus prohibiting fiduciary's guarantee to transfer it. The stock of goods in the warehouse can be burdened through the warehouse receipt guarantee institution, but does not provide protection to the creditors, while the borrower's default, because neither the LAW No. 9 year 2006 and PP No. 36 year 2007 do not regulate the procedures for the logging of rights The warranty on the Book of Guarantee rights, so it is related to the execution of the stock of goods that are burdened as collateral. Therefore, there needs to be a clarity related to the registration of warehouse receipt guarantee, so that the beneficiary rights of the recipient guarantee the warehouse receipt when the default borrowers are protected.